Modelling of a fault in Indo-Suture Zone of Ladakh Region - Reddy, C. D.; Singh, Sumendra (My University, 1995)
Magnetic field is measured along the Keylong-Leh profile. This profile is approximately aligned at right angles to the main structural trend of the Himalaya and traverses across several prominent thrust zones of middle Himalaya. Apart from the strong N-S trend, this profile is characterized by a pronounced anomaly near the boundary separating Indus formation from the Ladakh plutonic belt. The anomaly is inverted in terms of a fault model. The model which best produces the observations has southerly dip of 75o with its top and bottom surfaces at the depths about 1 and 20 km respectively. The model also requires a large susceptibility contrast between the Indus formation and Ladakh plutonic belt. It is surmised that plutonic belt with gabbro concentration of the order of 33% will be able to provide the desired susceptibility contrast.
Keywords: Indo-Tsangpo Suture Zone; Fault modelling